Mass of the Lightest Neutral CP-even Higgs in the Supersymmetric Minimal Reduced 3-3-1 Mode - Hung, Ha Thanh; Hue, Le Tho; Hang, Nguyen Thi Thu; Thu, Pham Ngoc (Communications in Physics, 2014)
We calculate the mass of the lightest neutral CP-even Higgs in the frame work of the supersymmetric reduced minimal 3-3-1 model (SUSYRM331) at one-loop level. Like MSSM, at tree level this value of mass is smaller than that of \(m_Z=92\) GeV, inconsistent with value of 125 GeV measured by recent experiment. In this work we prove that the mass of the lightest neutral CP-even Higgs will get the consistent value if loop corrections are included